Corneal Cross-Linking With Verteporfin and Nonthermal Laser Therapy. Issue 3 (March 2018) - Alageel, Saleh A.; Arafat, Samer N.; Salvador-Culla, Borja; Kolovou, Paraskevi E.; Jahanseir, Khadijeh; Kozak, Adam; Braithwaite, Gavin J. C.; Ciolino, Joseph B.
Abstract : Purpose: To test whether verteporfin with a nonthermal laser increases corneal mechanical stiffness and resistance to enzymatic degradation ex vivo. Methods: Thirty human corneas (n = 5 per group) were treated with verteporfin alone (V), irradiated with nonthermal laser therapy (689 nm) alone (NTL), or received combined treatment of verteporfin with nonthermal laser therapy for 1 sequence (V+NTL1) or 6 sequences (V+NTL6) of 1 minute of NTL exposure. Positive controls were pretreated with 0.1% riboflavin/20% dextran every 3 to 5 minutes for 30 minutes and irradiated with ultraviolet light type A (λ = 370 nm, irradiance = 3 mW/cm 2 ) for 30 minutes using the Dresden protocol (R+UVA). Untreated corneas were used as negative controls. The corneal biomechanical properties were measured with enzymatic digestion, compression, creep, and tensile strength testing. Results: V+NTL6- and R+UVA-treated corneas acquired higher rigidity and more pronounced curvature than untreated corneas. The stress–strain tests showed that V+NTL6 and R+UVA corneas became significantly stiffer than controls ( P < 0.005). The V+NTL6 group seemed to be slightly stiffer than the R+UVA group, although the differences were not statistically significant. V+NTL6 corneas were found to have a significantly lower absolute creep rate (−1.87 vs. −3.46, P < 0.05) and significantly higher maximum stress values (7.67 vs. 3.02 P < 0.05) compared with untreated corneas. Conclusions: Verteporfin-NTL (V+NTL6) increases corneal mechanical stiffness and resistance to enzymatic collagenase degradation. Although a clinical study is needed, our results suggest that V+NTL6 induces corneal cross-linking and corneal biomechanical changes that are similar to those induced by standard corneal collagen cross-linking. Abstract : Supplemental Digital Content is Available in the Text.